Towards Fostering Education of Future Health Workers: Exploring the Understanding of Work with People with Disabilities through Collage Method - Rūta Girdzijauskienė; Liudmila Rupšiene; Milda Ratkevičienė (Acta Paedagogica Vilnensia)
The healthcare system has long discussed the need to remove barriers faced by people with disabilities, however, health workers are often still not prepared to efficiently work with such people, and their education is still inadequate. This article explores future health workers’ understanding of the work with people with disabilities. The research study included five students from institutions of higher education studying in programmes training health workers. Research analysis included collages by two groups, transcripts of their presentations and researcher field notes. Analysis of the research study has helped to identify the topics of contextuality of professional activity and professional agency. When considering their future professional work with people with disabilities, students paid attention to the geographical (local), social and political contexts. The agency in the professional activity was expressed weakly. Research participants introduced several ideas how it would be possible to solve problems of people with disabilities. However, they did not consider actions how it could be done, nor did they make a connection between the changes in the healthcare system and their future professional activities. The article raised a question how to consolidate the education of future health specialists so that, after graduation, they would be able to work more efficiently with people with disabilities and meet their needs.